1975
DOI: 10.1111/j.1365-2184.1975.tb01501.x
|View full text |Cite
|
Sign up to set email alerts
|

Cell Kinetics of Irradiated Experimental Tumors: Relationship Between the Proliferating and the Nonproliferating Pool

Abstract: The role of nonproliferating cells in tumor regeneration has been studied after subcurative doses of low L.E.T. irradiation. Radiation was applied in a single dose at three different levels, 0–47, 0–94 and 1–88 krad. Studies included estimation of the absolute number of cells per tumor, differential cell counts, and autoradiographic determination of kinetic variables, employing transplantable mouse mammary adenocarcinoma DBAH. Quantitative changes of morphologically denned proliferating and non‐proliferating c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

1977
1977
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…Weichselbaum explained that the repair of radiation-induced molecular damage may be facilitated if DNA replication is delayed by holding cells in G1 (71 ). Potmesil and Goldfeder reported that nonproliferating G. confined cells from mouse mammary adenocarcinoma cell lines DBAH and MT2 persist in irradiated tumors of mice and a transition of these nonproliferating cells to the proliferating pool takes place at the start of tumor recurrence (67). In contrast, Wallen et al reported that quiescent cells from the murine mammary carcinoma cell lines 66 and 67 are significantly more sensitive than proliferating cells from the same cell lines (72).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Weichselbaum explained that the repair of radiation-induced molecular damage may be facilitated if DNA replication is delayed by holding cells in G1 (71 ). Potmesil and Goldfeder reported that nonproliferating G. confined cells from mouse mammary adenocarcinoma cell lines DBAH and MT2 persist in irradiated tumors of mice and a transition of these nonproliferating cells to the proliferating pool takes place at the start of tumor recurrence (67). In contrast, Wallen et al reported that quiescent cells from the murine mammary carcinoma cell lines 66 and 67 are significantly more sensitive than proliferating cells from the same cell lines (72).…”
Section: Resultsmentioning
confidence: 99%
“…CD34 cDNA predicts a 373-amino acid polypeptide that is a type I integral membrane protein and has no sequence homology to any known protein (58). Notably, > 30% of the predicted amino acids in the NH2-terminal domain of this antigen are serine or threonine residues and CD34 antigen is a substrate for protein kinase C (PKC) (58,61 (65)(66)(67)(68)(69). Kimler and Anderson reported that 9L rat brain tumor cells are most resistant to radiation while in G1 phase (70).…”
Section: Resultsmentioning
confidence: 99%
“…Proliferating cells are the target of most cancer therapies. The quiescent cell population has been implicated as a population resistant to some of these therapies, playing an important role in tumor regrowth (Potmesil and Goldfeder, 1980; Kallman et al, 1982). …”
Section: Introductionmentioning
confidence: 99%
“…The majority of the tumours in experimental animals has a growth fraction of <80%, and similar studies of labelled mitoses suggested even smaller growth fractions in a series of well-studied human tumours (Steel, 1977). Quiescent cells may be important in tumour eradication because they are probably more resistant to proliferation-dependent treatment regimens, and since they retain the capacity to proliferate, there are suggestions that they may be the source for renewed growth after cancer therapy (Hermans & Barendsen, 1978;Kallman et al, 1979;Luke et al, 1985;Potmesil & Goldfeder, 1980;Sutherland & Durand, 1976;Sutherland, 1974;Valeriote & van Putten, 1975). In previous studies, we have isolated and characterized a quiescent subpopulation from EMT6/Ro fed plateau monolayers, and found that those quiescent cells were smaller, mostly in the G1 phase of the cell cycle, had a lower cellular RNA content, were not labelled by [3H]-thymidine after 2 cell cycle times, retained the capacity to divide after replating into fresh medium, and were more sensitive to y-ray radiation (Luk et al, 1985).…”
mentioning
confidence: 99%